Determinants of maternal mental health during pregnancy: A systematic review - Hariet Rinancy; Rahmi Kurnia Gustin; Desti Natari; Mutia Felina (JOURNAL OF Mental Health Concerns, 2026)
Background: The mental health of pregnant women is a critical public health issue because it affects the well-being of both the mother and the foetus. Conditions such as antenatal depression and anxiety in pregnant women are common but often go undetected Purpose: To identify the determinants of mental health in pregnant women through a systematic review Method: This study employed a systematic review method to identify, evaluate, and synthesize scientific evidence regarding the determinants of mental health in pregnant women. The article was prepared in accordance with the PRISMA guidelines to ensure transparency and the replicability of the research. A systematic literature search was conducted in several databases, including PubMed, ScienceDirect, and Google Scholar. The search focused on articles published between 2020 and 2026 Results: Sociodemographic factors, obstetric conditions, social support, and access to health care are the primary determinants of mental health among pregnant women Conclusion: Community-based interventions and increased social support are needed to improve maternal mental health during pregnancy Keywords: Determinants; Mental Health; Pregnancy.